(untitled) (Research, Society and Development, 2022)
The Covid-19 disease became a pandemic in 2019, starting in China. This disease is being related to opportunistic infections, mainly fungal. One of these co-infections refers to the association with mucormycosis. Objective: In this sense, this study was carried out to evaluate the information available in the literature on the subject and to detect possible clinical conducts. Methodology: For this, the scope review methodology was used to gather information about possible treatments and clinical procedures related to this double infection. Results: 350 articles were found and at the end 13 articles were included in the analysis. Close follow-up of the patients was identified as the clinical procedure to be adopted, in order to identify any facial necrosis, and liposomal amphotericin B was identified as treatment. Conclusion: This knowledge helps the SUS to set up care strategies and robust clinical protocols in relation to this co-infection, which is still little known, as observed in the current literature.